Perkawinan pring sedapur : Tinjauan Urf’ dan Masalahah Mursalah - Dwi Sus Arianto; Nabila Luthvita Rahma (LPPM UIN Saizu Purwokerto, 2023)
The prohibition of pring sedapur marriage is a marriage performed between a man and a woman who have the exact same weton. Although the majority of the residents of Kedungsari Village are Muslims, they still think that if this marriage is carried out, it will bring disaster. This study aims to find out in detail the explanation of pring sedapur marriage and to find out the review of Islamic law against the prohibition of pring sedapur marriage in Kedungsari, Tayu District, Pati Regency. This study uses the field research method with a qualitative approach. The sources of data for this study were primary data sources and secondary data. The subjects of this study were weton experts, village elders, community leaders, religious leaders, and perpetrators of the marriage. Data collection techniques in this study were carried out by means of observation, interviews, and documentation. Based on the data collected and analysed, it can be concluded that: 1) The definition of pringsedapur marriage is a marriage performed by a man and a woman where the couple has the exact same weton. This tradition still applies in Kedungsari village because the community believes that if the marriage is carried out, it will bring disaster to the perpetrators of the marriage itself and their families. 2) The prohibition of pringsedapur marriage cannot be used as a benchmark that prevents marriage because it is not compatible with slamic law and not regulated in the Qur'an or hadits. In terms of 'urf including 'urf fasid, and maslahah mursalah including maslahah mulghah.